Prescription Habits of Scleral Lenses for the Management of Corneal Irregularity and Ocular Surface Disease Among Scleral Lens Practitioners. Issue 2 (14th February 2023) - Shorter, Ellen; Fogt, Jennifer; Nau, Cherie; Harthan, Jennifer; Nau, Amy; Schornack, Muriel
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To describe prescribing patterns of therapeutic scleral lenses (SLs) in the management of corneal irregularity and ocular surface disease among practitioners who prescribe SLs. Methods: Participants ranked treatment options for corneal irregularity and ocular surface disease in the order they would generally consider using them in an electronic survey. Median rank score for each option is reported, along with the percentage of participants assigning first place ranking to each option. The percentage of participants assigning first, second, or third place ranking to each option is also reported. Results: Seven hundred and seventy-eight practitioners participated. Scleral lenses are most frequently considered as the first choice for the management of corneal irregularity based on overall median rank, followed by corneal rigid lenses (rigid gas-permeable [RGPs]). Scleral lenses were the first choice of 42% of participants, followed by RGPs (20%). For ocular surface disease, lubricant drops are most frequently used first, followed by meibomian gland expression, topical cyclosporine or lifitegrast, topical steroids, punctal plugs, and SLs, respectively. Lubricant drops were the first therapeutic option considered for ocular surface disease by 63% of participants and 45% ranked SLs as their sixth, seventh or eighth treatment based on median overall rank. Conclusions: Scleral lenses were identified as the first option for management of corneal irregularity more frequently than RGPs. Scleral lenses are considered for management of ocular surface disease before surgical intervention but after meibomian gland expression, punctal occlusion, and topical medical therapy are attempted.